Broad scope and narrow focus: On the contemporary linguistic and psycholinguistic study of third language acquisition. (December 2017) - Alonso, Jorge González; Rothman, Jason; Berndt, Denny; Castro, Tammer; Westergaard, Marit
Aims: in this introduction we situate the seven articles in this special issue in terms of the connections between their themes and their individual contributions to the field of third language acquisition (L3A): new theoretical models, innovative methodologies, an epistemological commentary and new perspectives related to multilingual processing and cognitive function. Approach: we discuss important and often overlooked differences between bi- and multilingualism in the context of second language versus third or further language acquisition. We also provide a brief historical overview of the relatively young field of L3A and outline the three current models of linguistic transfer in L3 morphosyntax. Finally, we approach the issues of methodology, psychological complexity and cognitive implications that are discussed in some of these papers. Conclusions: the diversity of topics in these articles endows the issue with a broad approach to the field of L3A, while individual articles offer a narrow focus on specific theoretical and methodological issues. Significance: this special issue provides an accurate portrayal of the current interest in, and rapid expansion of, multilingualism within linguistic and psycholinguistic approaches.